Informing Employees in Small and Medium Sized Firms about Training: Results of a Randomized Field Experiment - Gerard J. van den Berg; Christine Dauth; Pia Homrighausen; Gesine Stephan (Institute of Labor Economics (IZA), 2018)
We analyze a German labor market program that subsidizes skill-upgrading occupational training for workers employed in small and medium sized enterprises. This WeGebAU program reimburses training costs but take-up has been low. In an experimental setup, we mailed 10,000 brochures to potentially eligible workers, informing them about the importance of skill-upgrading occupational training in general and about WeGebAU in particular. Using combined survey and register data, we analyze the impact of receiving the brochure on workers' awareness of the program, on take-up of WeGebAU and other training, and on job characteristics. The survey data reveal that the brochure more than doubled workers' awareness of the program. We do not find effects on WeGebAU program take-up or short-run labor market outcomes in the register data. However, the information treatment positively affected participation in other (unsubsidized) training among employees under 45 years.
Keywords: J24; J65; 330; information treatment; wages; skills; employment; randomized controlled trial